Combined Effects of Prenatal Polycyclic Aromatic Hydrocarbons and Material Hardship on Child IQ - Vishnevetsky, Julia (Neurotoxicol Teratol, 2015)
IMPORTANCE: Polycyclic aromatic hydrocarbons are common carcinogenic and neurotoxic urban air pollutants. Toxic exposures, including air pollution, are disproportionately high in communities of color and frequently co-occur with chronic economic deprivation. OBJECTIVES: We examined whether the association between child IQ and prenatal exposure to polycyclic aromatic hydrocarbons differed between groups of children whose mothers reported high vs. low material hardship during their pregnancy and through child age 5. We tested statistical interactions between hardships and polycyclic aromatic hydrocarbons, as measured by DNA adducts in cord blood, to determine whether material hardship exacerbated the association between adducts and IQ scores. DESIGN: Prospective cohort. Participants were recruited from 1998 to 2006 and followed from gestation through age 7 years. SETTING: Urban community (New York City) PARTICIPANTS: A community-based sample of 276 minority urban youth EXPOSURE MEASURE: Polycyclic aromatic hydrocarbon-DNA adducts in cord blood as an individual biomarker of prenatal polycyclic aromatic hydrocarbon exposure. Maternal material hardship self-reported prenatally and at multiple timepoints through early childhood. MAIN OUTCOME MEASURE: Child IQ at 7 years assessed using the Wechsler Intelligence Scale for Children. RESULTS: Significant inverse effects of high cord PAH-DNA adducts on full scale IQ, perceptual reasoning and working memory scores were observed in the groups whose mothers reported a high level of material hardship during pregnancy or recurring high hardship into the child’s early years, and not in those without reported high hardship. Significant interactions were observed between high cord adducts and prenatal hardship on working memory scores (β=−8.07, 95% CI (−14.48, −1.66) and between high cord adducts and recurrent material hardship (β=−9.82, 95% CI (−16.22, −3.42). CONCLUSION: The findings add to other evidence that socioeconomic disadvantage can increase the adverse effects of toxic physical “stressors” like air pollutants. Observed associations between high cord adducts and reduced IQ were significant only among the group of children whose mothers reported high material hardship. These results indicate the need for a multifaceted approach to prevention.